Pengaruh Hygiene Factor dan Motivator Terhadap Kepuasan Kerja dan Kinerja Karyawan Pada Mitra Kerja PT. PLN (PERSERO) Unit Induk Pembangunan (UIP) Nusa Tenggara - Suprayetno, Djoko; Kusmayadi, Iwan; Suryatni, Mukmin; Nururly, Santi; Nurmayanti, Siti (Postgraduate, University of Mataram, 2025)
This study aims to determine the influence of hygiene factors, motivators on job satisfaction and employee performance of PT. PLN (Persero) Nusa Tenggara Development Main Unit (UIP). The type of research used in this study is causal associative research, namely to determine the influence of hygiene factors, motivation factors on job satisfaction and performance of PT. PLN (Persero) UIP NUSRA. The data collection method used in this study is the Census Method, because the number of population in this location is 51 people so that all populations become research respondents. The analysis technique used is path analysis. The results obtained are hygiene factors, motivators have a significant effect on job satisfaction and hygiene factors, job satisfaction has a significant effect on employee performance, unless motivators do not have a significant effect on employee performance.